Penguatan Perilaku SEE (Self-Assertiveness, Empathy & Emotional Regulation) Sebagai Upaya Pencegahan Bullying Pada Siswa Madrasah Aliyah - Ishlakhatus Sa'idah; Diana Vidya Fakhriyani; Akmalul Umam; Jenius Dwi Pangestu (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Bullying in educational settings remains a serious issue with negative impacts on students' social and emotional well-being. This community service program aims to strengthen Self-Assertiveness, Empathy, and Emotional Regulation (SEE) behaviors as a preventive strategy to reduce bullying tendencies at Madrasah Aliyah Al-Djufri Blumbungan Pamekasan. The activity uses a Participatory Action Research (PAR) approach, involving 40 students from grades X–XII and guidance and counselling teachers as collaborative partners. The implementation was conducted in four sessions, including social identification, material delivery, role-playing bullying phenomena, and reflective games to strengthen social-emotional skills. The effectiveness of the program was measured using pretests and posttests with a four-dimensional bullying scale (verbal, physical, social, and cyber). The analysis results showed a significant decrease in all aspects with a p-value < 0.001 and an average decrease of 42.2%. Qualitative findings revealed an increase in empathy, assertive courage, and more adaptive emotional regulation abilities. This program also encourages the formation of SEE Ambassadors as agents of change in creating an empathetic and violence-free school climate. This activity underscores the effectiveness of the SEE-based participatory and reflective approach in bullying prevention while also strengthening humanistic and character-based Islamic educational practices.